RAISING LECTURER’S ABILITY TO ASK THROUGH CREATIVE DIALOGUE AFFECTS THE IMPROVEMENT OF PANCASILA LEARNING OUTCOMES ON I AH STUDENTS AT STATE POLYTECHNIC OF SRIWIJAYA PALEMBANG - Zaliah -; Hadi Winarko; Aimi - (HOLISTICS, 2017)
As the basis of the state, Pancasila must be understood and performed in order to uphold The Unitary State of the Republic of Indonesia (NKRI). Therefore, Pancasila must be studied in various strategies to enhance the learning quality, one of which is creative dialogue model. In another word expository shifter (imperative dialogue) to the creative dialogue. Overall, this research indicates that the learning process using creative learning model may increase the percentage of student’s activeness and learning outcome. The activeness percentage of students in cycle II shows that from 23 students, 16 students or 69,56% of the students obtain very active percentage and 7 students or 30,53% of the students obtain active percentage thus the learning activeness increase 21,73% from cycle I. From the data analysis, 18 students or 78,26% of the students obtain score over the minimum passing grade (≥65) and 5 students or 21,73% obtain ≤ 65. Thus, completion percentage increase 30,44%.